STRATEGI PERIKLANAN DALAM MEMBANGUN PERSONAL BRANDING PUTRI ARISTIANI SEBAGAI BEAUTY ENTHUSIAST PADA MEDIA SOSIAL INSTAGRAM - Suryono, Joko; Widiastuti, Oktavia (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2025)
Instagram is a potential medium in building personal branding, especially in the beauty field. Putri Aristiani, a beauty enthusiast, utilizes this platform to build her self-image. This research aimed to find out the advertising strategy used by Putri and identify the challenges faced, by analyzing it through Peter Montoya's The Eight Laws of Personal Branding theory, which includes: specialization, leadership, personality, difference, visibility, unity, constancy, and good name. This research used descriptive qualitative methods with in-depth interview techniques, observation by listening to Putri Aristiani's Instagram content (@putriaristiani05) and questionnaires to followers. The results showed that the advertising strategy used includes selectivity in choosing products, soft selling approach, personal and educational communication style, and visual consistency. Putri actively built interactions with followers and chooses products that match her personal values, such as Wardah and NAMA Beauty. Despite facing challenges such as changes in the Instagram algorithm, Putri maintained consistency and relevance of content. The strategy applied reflected a strong effort in building a self-image that is authentic, credible and in line with the personal identity displayed on social media.